Proposed technical architectural framework supporting heterogeneous applications in a hospital. (2016) - Zarour, Karim
Nowadays, hospital information systems (HISs) play a crucial role in helping medical staffs in accomplishing their daily tasks. In a hospital, actors with different profiles accomplish a variety of activities. In such a context, the processed information is variable in nature and large in quantity. The actors who may be distant, as inside, from the hospital are likely to use heterogeneous application systems. The shared data, which are exchanged in the form of records, require flexibility of access. This paper proposes a new architectural framework for an Algerian hospital system where heterogeneity of applications is involved. The proposed architecture comprises all necessary components for its well functioning.